Pengaruh Dukungan Sosial, Self-Esteem Dan Self-Efficacy Terhadap Burnout Mahasiswa (Studi Pada Mahasiswa Universitass Islam Malang) - Moh Lutf; Ronny Malavia Mardani; Ita Athia (E-JRM : Elektronik Jurnal Riset Manajemen, 2022)
AbstractThis study aims to determine the effect of social support, self-esteem, self-efficacy and This study aims to determine the effect of social support, self-esteem, self-efficacy and student burnout on students at the Islamic University of Malang. The location of this research was conducted on students of the Islamic University of Malang. This research is a quantitative research. This research uses a case study method where data is obtained by distributing questionnaires to students of the Islamic University of Malang who were selected by purposive sampling. Determination of the number of samples using the Slovin formula and the results obtained were 99 respondents. Data were analyzed using multiple linear regression and determination test. Based on the results of data analysis, the results of the t-test indicate that social support partially has a negative but significant effect on student burnout at the Islamic University of Malang. The results of the t test show that self-esteem, self-efficacy partially have a significant positive effect on student burnout at the Islamic University of Malang students. The results of the determination test showed that the percentage was 33.8%, in which student burnout was able to be influenced by social support, self-esteem, and self-efficacy. Keywords: Student Burnout, Social Support, Self-esteem, Self-efficacy